Preparação e caracterização de microemulsões contendo fluconazol - Carnicel, Carolina (2014)
Microemulsions are dispersions of oil and water stabilized by surfactants and co-surfactants. These systems are defined as thermodynamically stable, isotropic, optically colorless and with low viscosity. Microemulsions have applications as a drug delivery system cause enhancing drug absorption and they are in many cases more efficient than other methods. The aim of this work was to prepare and characterize microemulsions that could be applied as a topical delivery system of fluconazol. Microemulsion systems were obtained from isopropyl myristate, water and various mixtures of surfactants and co- surfactants. For the development of microemulsions pseudoternay phase diagrams were used through the 36 formulations which were prepared with proportions of components (water, oil and surfactant) from 10 to 80%. The interaction between the drug and the vehicle was investigated using spectra of microemulsion and fluconazole obtained by infrared spectroscopy, the size particle and zeta potencial were mensured using zeta potential. Microemulsions approved by the stability test were incorporated with fluconazole 2% and tested for antifungal activity in Candida albicans. The formulations were more stable after stability studies were called 7C and 15C, these formulations when incorporated with the drug kept the physicochemical stability and infrared spectrophotometry was observed that there was no interaction between the drug and vehicle, most formulation showed zeta potential within range of stability (more 25 mV), the particle diameter varied between 238 and 429nm, where the formulation 7CF showed better antifungal activity against Candida albicans.